2024
DOI: 10.1021/acs.jpca.3c07404
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Kinetics for the Oxidation of Californium(III) Ions with Select Radiation-Induced Inorganic Radicals (Cl2•– and SO4•–)

Brian M. Rotermund,
Stephen P. Mezyk,
Joseph M. Sperling
et al.

Abstract: Despite the availability of transuranic elements increasing in recent years, our understanding of their most basic and inherent radiation chemistry is limited and yet essential for the accurate interpretation of their physical and chemical properties. Here, we explore the transient interactions between trivalent californium ions (Cf 3+ ) and select inorganic radicals arising from the radiolytic decomposition of common anions and functional group constituents, specifically the dichlorine (Cl 2•− ) and sulfate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 84 publications
(177 reference statements)
1
1
0
Order By: Relevance
“…The ambient temperature rate for eqn (8) is consistent with those reported for the few other measured trivalent actinides: plutonium (2.50 × 10 8 M −1 s −1 ), 45 curium ((4.83 ± 0.09) × 10 7 M −1 s −1 ), 41 and californium ((1.78 ± 0.06) × 10 8 M −1 s −1 ). 42,46 Comparison of these values with the associated IV/III redox couples (ESI, Fig. S13†) 2 demonstrates that single electron transfer to NO 3 ˙ becomes less energetically favourable with increasing reduction potential, as expected.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…The ambient temperature rate for eqn (8) is consistent with those reported for the few other measured trivalent actinides: plutonium (2.50 × 10 8 M −1 s −1 ), 45 curium ((4.83 ± 0.09) × 10 7 M −1 s −1 ), 41 and californium ((1.78 ± 0.06) × 10 8 M −1 s −1 ). 42,46 Comparison of these values with the associated IV/III redox couples (ESI, Fig. S13†) 2 demonstrates that single electron transfer to NO 3 ˙ becomes less energetically favourable with increasing reduction potential, as expected.…”
supporting
confidence: 60%
“…40 That said, more recent studies have shown that NO 3 ˙ is capable of transiently oxidizing trivalent actinides with formally higher IV/III couples, such as curium ( E ° = 3.1 V SHE ) and californium ( E ° = 3.2 V SHE ). 24,41,42 Consequently, NO 3 ˙ may have the capacity to transiently generate Am( iv ), providing the opportunity to study this non-equilibrium oxidation state under conditions more frequently encountered in fundamental and applied americium manipulations.…”
mentioning
confidence: 99%